1995
DOI: 10.1288/00005537-199511000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic adnexal carcinoma: Management options based on long‐term follow‐up

Abstract: Microcystic adnexal carcinoma (MAC), a recently described neoplasm that frequently affects the head and neck, presents a confusing problem for the clinician due to its unusual behavior. The individual cells have a bland microscopic appearance, and there is a predilection for neural invasion. Four cases of MAC are reported. All four cases demonstrate the difficulty with pathologic diagnosis. Follow-up of as long as 33 years begins to delineate the protracted nature of MAC. In addition, this paper includes the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
144
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(146 citation statements)
references
References 13 publications
1
144
1
Order By: Relevance
“…Mitotic structures are rare in these tumor cells, and they lack significant atypia. MAC tumor cells invade the whole dermis, frequently invading the striated muscle, nerves, vascular adventitia, cartilage tissue and periosteum (1)(2)(3)13). Although MACs have the ability to locally invade tissues, very few cases have reported systemic metastasis and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mitotic structures are rare in these tumor cells, and they lack significant atypia. MAC tumor cells invade the whole dermis, frequently invading the striated muscle, nerves, vascular adventitia, cartilage tissue and periosteum (1)(2)(3)13). Although MACs have the ability to locally invade tissues, very few cases have reported systemic metastasis and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are required to identify a reliable immunohistochemical marker specific to MACs. Therapy for MACs remains a challenge, as the tumor-free margin is significantly more extensive than can be determined clinically and the tumors exhibit a marked tendency for perineural invasion (3)(4)(5). Numerous treatment modalities have been used to date, including standard excision (SE), MMS, irradiation and chemotherapy (6,16); however, a number of studies have found that MAC is not sensitive to radiotherapy and chemotherapy (5,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations